2020
DOI: 10.1038/s41467-020-19078-0
|View full text |Cite
|
Sign up to set email alerts
|

Metal chalcogenide hollow polar bipyramid prisms as efficient sulfur hosts for Na-S batteries

Abstract: Sodium sulfur batteries require efficient sulfur hosts that can capture soluble polysulfides and enable fast reduction kinetics. Herein, we design hollow, polar and catalytic bipyramid prisms of cobalt sulfide as efficient sulfur host for sodium sulfur batteries. Cobalt sulfide has interwoven surfaces with wide internal spaces that can accommodate sodium polysulfides and withstand volumetric expansion. Furthermore, results from in/ex-situ characterization techniques and density functional theory calculations s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
105
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(106 citation statements)
references
References 48 publications
(70 reference statements)
1
105
0
Order By: Relevance
“…[ 16a ] However, the peak intensity was maintained at about 0.39 after interaction between CFC and Na 2 S 6 , indicating the limited polysulfide trapping ability (62% sulfur lost) just based on physical confinement. [ 18 ] Aligning with our expectations, a stable Na‐S cell can be obtained if certain sulfur host was designed. Intensity reduction and position shift of the retrieved sample in XPS spectra confirms the existence of chemical interaction (Figure 2b).…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…[ 16a ] However, the peak intensity was maintained at about 0.39 after interaction between CFC and Na 2 S 6 , indicating the limited polysulfide trapping ability (62% sulfur lost) just based on physical confinement. [ 18 ] Aligning with our expectations, a stable Na‐S cell can be obtained if certain sulfur host was designed. Intensity reduction and position shift of the retrieved sample in XPS spectra confirms the existence of chemical interaction (Figure 2b).…”
Section: Resultssupporting
confidence: 67%
“…As illustrated in Figure 3c, when the CFC/S@FC‐PPy||Na cell is discharged from 1.7 to 1.0 V, the long‐chain and short‐chain polysulfides Raman vibrational peaks were diminished and just one peak at ≈428 nm, indexed to the Na 2 S characteristic peak, was generated at the fully discharged state. [ 4a,6a,18a ] This means that FC‐PPy can catalyze Na 2 S 4 complete conversion. While some irreversible Na 2 S 2 was reflected in the XRD patterns in CFC/S@PPy electrode (see Figure 3d), indicating that the confined intermediates are more fully reduced to the final discharged product in CFC/S@FC‐PPy than in CFC/S@PPy and CFC/S, agreeing well with CV and GCD results above.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, metal and metal compounds show high chemical adsorption capabilities with intermediate polysulfides. [88][89][90] Therefore, a more reasonable approach is to design hybrid hosts that combine highly conductive carbonaceous materials with highly polar compounds such as metals, [91][92][93][94][95] metal oxides, [96,97] metal sulfides, [98][99][100][101][102] metal carbides, [103,104] metal phosphides, [105] and metal oxyhydroxides. [106] Taking molybdenum disulfide (MoS 2 ) as a typical example; Xu et al prepared a sulfur carrier of hollow carbon spheres decorated with MoS 2 nanosheets (Figure 7a).…”
Section: Carbon/sulfur and Other Sulfur Composite Cathodesmentioning
confidence: 99%
“…[75,79,81,[90][91][92][93]95,98,99,101,102,153] In situ synchrotron XRD is a powerful technique to probe the crystallographic intermediates, which has been widely employed in the mechanistic studies of MSBs. [75,79,90,91,95,99,102] For instance, Dou et al conducted in situ XRD to track the conversions of intermediate polysulfides under different working stages, as shown in Figure 15a. [91] They showed that cobalt catalyzed Na 2 S 4 into elemental sulfur during the charge process, whereas irreversible Na 2 S 4 species were detected without the cobalt catalyst.…”
Section: Advanced Characterization Techniquesmentioning
confidence: 99%